Contaminación acústica generada por el ruido vehicular y sus efectos en los habitantes de la zona norte de la ciudad de Loja - Armijos Díaz, Alex Xavier (2019)
In the northern zone of the city of Loja, vehicular noise pollution is permanent, especially in the streets with the highest traffic levels, affecting the health of the inhabitants, an aspect verified by Correa and Jara (2014). The present research consisted of evaluating noise pollution in the northern zone of the city and the cause-effect relationship between noise levels and the appearance of psychosomatic disorders that affect people's health; sound pressure levels were established, negative health impacts were identified and alternatives for noise control were proposed. In the measurement of noise levels was taken a total of 225 points divided into two sectors, the measurements were made for 10 minutes with three repetitions and three different times (07H00 - 09H00, 11H00 - 13H00 and 17H00 -19H00), parallelly counted vehicles differentiated by categories. The effects of noise on the health of the inhabitants were determined through the application of a questionnaire applied to a population by means of a simple systematic random sampling and alternatives were built on the basis of the results obtained and with secondary information from different noise management studies. The main results showed that the noise levels in the main streets of the northern zone exceed the 65 dB allowed, except for Ambato and Babahoyo streets, however, in the secondary streets the higher noise levels are generated at specific points, a fact that is corroborated in the noise maps made. The main effects on health found are: stress, headache and difficulty in falling asleep, considering alternatives for controlling and reducing noise: restriction of access to heavy vehicles, alternative traffic routes, better signage, awareness campaigns, soundproofing houses, placing acoustic barriers, promoting mobility on foot and by bicycle, among others. The study concludes that mobile sources are the main generators of noise, increasing this: the increase in the number of vehicles, lack of signage, heavy vehicles and width of the road, highlighting the improper use of the horn and implementation of resonators in motorcycles. Keywords: vehicle noise, noise pollution, noise maps